Knowledge, attitude, and adherence to malaria control guidelines and the prevalence of Plasmodium species infection in localities across transmission and ecological zones in Cameroon - Tangi, Livinus N.; Ajonina, Marcelus U.; Moyeh, Marcel N.; Chi, Hanesh F.; Ntui, Vincent N.; Kwi, Pilate N.; Toussi, Eric C. T.; Fung, Mary Progress S.; Fah, FohTella; Mayaba, Joel M.; Formilack, Franklin T.; Ntasin, Veronica N.; et al. (Frontiers in Public Health, 2023)
Background Despite a scale up of control interventions over the years, malaria remains a major public health and economic concern in Cameroon, contributing considerably to hospitalisation and deaths. The effectiveness of control strategies depends on the extent of adherence by the population to national guidelines. This study assessed the influence of human knowledge, attitudes, and practices related to malaria and its control on the prevalence of malaria parasite infection, with implications for the elimination of the disease. Methodology This is a cross-sectional community and hospital-based study, covering the five ecological and three malaria transmission zones in Cameroon. A pre-tested semi-structured questionnaire was used to document socio-demographic and clinical parameters as well as knowledge, attitudes, and practices towards malaria control and management. Consenting participants were screened for malaria parasite with rapid diagnostic test (mRDT) of the peripheral blood. Association between qualitative variables was determined using the chi-square test and logistic regression analysis. Results A total of 3360 participants were enrolled, 45.0% (1513 of whom were mRDT positive, with 14.0% (451/3216) and 29.6% (951/3216) having asymptomatic parasitaemia and malaria respectively. Although most participants knew the cause, symptoms, and control strategies, with 53.6% (1000/1867) expertly knowledgeable about malaria overall, only 0.1% (2/1763) individuals were fully adherent to malaria control measures. Conclusion The risk of malaria in Cameroon remains high, with the population considerably knowledgeable about the disease but poorly adherent to national malaria control guidelines. Concerted and more effective strategies aimed at improving knowledge about malaria and adherences to control interventions are necessary to ultimately eliminate the disease.